Bilateral Knee Dislocations Treated with Acute, Single-Stage Multiligament Reconstructions - Casey Imbergamo; Andrzej Brzezinski; Tiffany Smith; Patrick S. Buckley; Kenneth G. Swan (Case Reports in Orthopedics)
Bilateral knee dislocations are exceedingly rare in orthopaedics. Managing these injuries presents a difficult task given their high complication rate and guarded prognosis. We report the case of a 21-year-old male who presented to our institution with bilateral knee dislocations sustained in a motor vehicle collision. The patient subsequently underwent multiligament knee reconstruction surgeries for each knee at one and three weeks following the initial injury. At one-year follow-up, the patient has achieved a successful outcome and has returned to regular activities which include hiking and exercising at the gym.